Dinamika Sengketa Perdata Islam di Pengadilan Agama Daerah Istimewa Yogyakarta - M Khoirur Rofiq (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2020)
The authority of the Religious Courts is regulated in Law Number 7 of 1989, then changed to Law Number 3 of 2006, and changed back to Law Number 50 of 2019. Inside it explained that the Religious Court has the authority to examine, decide upon, resolve cases at the first level among people who are Muslim in the fields of marriage, inheritance, wills, grants, endowments, zakat, infaq, shadaqah, and sharia economics. The purpose of this study is to describe the dynamics of the case in the Yogyakarta Religious Court in accordance with its legal authority (2010-2014). The exercise of authority of the Religious Courts in Yogyakarta has been carried out in accordance with the applicable laws and regulations, the types of disputed cases include family and sharia economic matters which are divided into several cases; (1) Polygamy, (2) Prevention of Marriage and Cancellation of Marriage, (3) Rights and Obligations of Husband and Wife, (4) Divorce Cases, (5) Sharing of Common Assets, (6) Disputes over the Rights of the Child, (7) Cases of Child Endorsement , (8) Revocation of Parental Power from Children, (9) Case of Guardianship, (10) Proof of Child's Origin, (11) Marriage Isbat, (12) Application for Marriage Permit and Marriage Dispensation, (13) Case of Guardian Adhol, ( 14) Shari'a Economic Cases, (15) inheritance disputes, (16) Probate disputes, (17) Grant disputes, (18) Wakaf property management disputes, (19 Requests for determining inheritance assets distribution.